2020
DOI: 10.3389/fbioe.2020.00616
|View full text |Cite
|
Sign up to set email alerts
|

A Polydopamine-Functionalized Carbon Microfibrous Scaffold Accelerates the Development of Neural Stem Cells

Abstract: Neuroregenerative medicine has witnessed impressive technological breakthroughs in recent years, but the currently available scaffold materials still have limitations regarding the development of effective treatment strategies for neurological diseases. Electrically conductive micropatterned materials have gained popularity in recent years due to their significant effects on neural stem cell fate. Polydopamine (PDA)—modified materials can also enhance the differentiation of neurons. In this work, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In addition, vincristine, a kind of cytoskeleton protein, is closely related to local adhesion and regulates cell proliferation. The expression of vincristine in NSCs cultured with PDA was enhanced significantly, and it showed that NSCs were much more proliferative than the non-PDA treatment group (Yang et al, 2020).…”
Section: Pda and The Activity Of Neuron And Neuron-likecells Nsc Adhementioning
confidence: 95%
“…In addition, vincristine, a kind of cytoskeleton protein, is closely related to local adhesion and regulates cell proliferation. The expression of vincristine in NSCs cultured with PDA was enhanced significantly, and it showed that NSCs were much more proliferative than the non-PDA treatment group (Yang et al, 2020).…”
Section: Pda and The Activity Of Neuron And Neuron-likecells Nsc Adhementioning
confidence: 95%
“…Spiral ganglion neurons lack the ability to regenerate after damage in the mammalian cochlea, which is a major cause of auditory neuropathy and may compromise the therapeutic effects of cochlear implants ( Guo et al, 2019 ). Extensive studies have been performed using neural stem cells for regeneration of neurons and the SGNs ( Fang et al, 2019 ; Li et al, 2019 ; Tang et al, 2019 ; Han et al, 2020 ; Xia et al, 2020 ; Yang et al, 2020 , 2021 ; Yuan et al, 2021 ). Yet, functional regeneration of SGNs from the resident glial cells may represent a novel strategy for hearing restoration caused by SGN damages.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss could be caused by genetic factors, aging, infectious diseases, ototoxic drugs, and noise exposure [1][2][3][4][5][6]. The reported mechanisms of noise-induced hair cells (HCs) and spiral ganglion neuron damage mainly include mechanical shearing forces and oxidative damage to HCs [7] and glutamate excitotoxicity to neurons [8][9][10][11]. In the past, noise exposure was considered harmful only when it causes a per-manent threshold shift (PTS) [3,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%